A study of English loan words in selected Bahasa Melayu newspaper articles - Shamimah binti Haja Mohideen (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2006)
This research deals with language contact between English and Bahasa Melayu, two important languages in Malaysia, which began from the British colonization and continues long after independence. Bahasa Melayu is the national language in Malaysia, while English is a second language and the international language as well as the language of specialization. English has had a lot of influence in Malaysia. The language contact is one way, where Bahasa Melayu tends to borrow numerous English words, rather than vice-versa, as English seems to be the dominant language. As more English words creep into Bahasa Melayu the purists of Bahasa Melayu have been concerned that English is linguistically conquering Bahasa Melayu, and therefore,it may lose its identity. This research has been conducted to study how English has contributed to enriching Bahasa Melayu vocabulary and facilitating communication, as well as how English has interfered with the language. The study has been conducted by means of textual analysis where the researcher has studied the function of English loanwords in the context of the selected Bahasa Melayu articles. From the loanwords identified, the researcher categorized the words according to those with equivalent and without equivalent. Based on the words with equivalents, surveys presenting pairs of English loanwords and their Malay equivalents were also distributed to respondents to find out their preference, and the findings revealed that the English loanwords were generally preferred over their Malay equivalents. This study goes beyond merely identifying loanwords because lexical borrowing does not merely reflect the borrowing of words. From a sociolinguistic perspective, there is historical significance in lexical borrowing. The loanwords identified from this study reflect social, political, educational and mental development as well as changes in trend and lifestyle and cultural influence in a community. This study revealed that there are several linguistic factors such as semantic factors as well as extralinguistic factors such as pragmatic, social and psychological factors and modern development that lead to the borrowing and preference for English words.